Modeling of psychological and pedagogical program of prevention of extremist tendencies of youth - Alexander V. Sharapov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article discusses the content of psycho-pedagogical programme for the prevention of extremist trends of the youth. The growth of extremist crimes, and the urgency of the development of preventive measures among young people are being noted. It formulates the basic idea of the program, the objectives, functions and principles of its realization. It determines four basic components of the programme and the description of working methods. To achieve effective results, the program includes training exercises, role plays, solving cases, items of folk and literary art (proverbs, sayings, poems) and questionnaires. The criteria for the assessment of program effectiveness are being proposed: the decline in the level of social frustration, negativity, aggression and hostility, and the desire for constructive ways of communication. The variability of the methodological material provides broad opportunities for its application in educational institutions with the aim of implementing prevention of extremist trends of the youth.